CUSTOMARY CONFLICT RESOLUTION MECHANISM AMONG THE GURAGE ZONE: A CASE STUDY OF MESKAN WOREDA, SOUTHERN ETHIOPIA - Wondu Lemu Said (International Scientific and Current Research Conferences, 2023)
This study focuses on exploring the customary conflict resolution mechanism among the Gurage Zone, with a specific case study conducted in Meskan Woreda, Southern Ethiopia. Customary conflict resolution mechanisms play a significant role in many societies, including the Gurage community, where traditional norms and practices are deeply ingrained. The study aims to examine the processes, procedures, and effectiveness of customary conflict resolution mechanisms in addressing disputes and maintaining social harmony within the Gurage Zone. Data were collected through interviews, focus group discussions, and observation of actual conflict resolution sessions. The findings shed light on the various stages of the conflict resolution process, the roles of key stakeholders, and the cultural and social factors influencing the effectiveness of the mechanisms. The study contributes to a better understanding of indigenous conflict resolution systems in Ethiopia and provides insights for policymakers and practitioners in fostering effective and culturally appropriate dispute resolution strategies.